2022
DOI: 10.1108/jtf-04-2022-0132
|View full text |Cite
|
Sign up to set email alerts
|

A “new tourism cycle” on the Canary Islands: scenarios for digital transformation and resilience of small and medium tourism enterprises

Abstract: PurposeThis paper discusses plausible future scenarios for small and medium tourism enterprises (SMTEs) in the “sun, sea and sand” destination of the Canary Islands (Spain) and assesses to what extent they are prepared to adjust to market changes and technological developments in the light of both sudden disruptions and long-term shocks.Design/methodology/approachA scenario analysis was made based upon expert interviews, leading to a 2 × 2 scenario matrix.FindingsAlthough regional, national and European strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The work of Hernández Sánchez and Oskam (2022) has demonstrated that the SMTEs in the Canary Islands remain vastly unprepared for shocks to the tourism industry. There is minimal resilience across the board, but in particular, those who have not embraced digital transformation are at most risk.…”
Section: Changing Requirementsmentioning
confidence: 99%
“…The work of Hernández Sánchez and Oskam (2022) has demonstrated that the SMTEs in the Canary Islands remain vastly unprepared for shocks to the tourism industry. There is minimal resilience across the board, but in particular, those who have not embraced digital transformation are at most risk.…”
Section: Changing Requirementsmentioning
confidence: 99%
“…They are often deeply connected to the communities in which they operate, contributing to the socio-economic fabric of the region (Coles et al, 2017). However, SMTEs face various challenges, including limited resources, access to finance, market competition, and vulnerability to external factors like economic downturns or global crises (Hernández Sánchez & Oskam, 2022). Supporting the growth and sustainability of SMTEs is crucial for fostering a resilient and inclusive tourism industry.…”
Section: Small and Medium-sized Tourism Enterprises (Smtes)mentioning
confidence: 99%
“…The digitization of SMTEs has become a crucial aspect, representing a shift from conventional systems to digital systems as an effort to enhance the effectiveness and efficiency of its business and operational processes (Ngoasong, 2018). Numerous studies have explored the connection between digitization, partnership networks, and branding in the development of Micro-, Small, and Medium-sized Enterprises (MSMEs) in the tourism 16,2 industry (Ashari et al, 2014;Collins et al, 2003;Hernández Sánchez & Oskam, 2022;Kurniawati et al, 2022). Digitization of SMTEs prompts stakeholders in the creative economy to transform their business management from conventional practices to modern ones (Moza & Ban, 2023).…”
Section: Small and Medium-sized Tourism Enterprises (Smtes)mentioning
confidence: 99%
“…Digital transformation is one of the leading innovative approaches for tourism enterprises to solve operational issues and strategic opportunities (S anchez and Oskam, 2022;Woolley and Lim, 2023); the digital transformation of tourism enterprises has solved operational issues and strategic opportunities and leveraged data analytics to gain insights into customer behavior, preferences, and market trends, enabling better decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…The gaps between the study and prior research include prior research focused on the digital marketing of tourism enterprises (Dewantara et al, 2022;Gutierriz et al, 2023); that research needs more exploration into the impact of digital transformation on tourism supply chain competition. On the other hand, many studies have emphasized that digital transformation is an essential strategy for tourism enterprises facing the threats and challenges of the epidemic (S anchez and Oskam, 2022;Tang and Huang, 2023). Furthermore, few studies have discussed the role of technology interoperability in the advantages of tourism products and supply chain resilience; technology compromise will influence the digital transformation of tourism enterprises.…”
Section: Introductionmentioning
confidence: 99%